Examining women [in]equality under the UN agenda 2030 and Africa Agenda 2063: between rhetoric and reality - Hafte Gebreselassie Gebrihet; Aster Asgedom Reda; Mulubrhan Atsbaha Geremedhn; Samuel Ataklti Abebe (Cogent Social Sciences, 2024)
The UN Agenda 2030 and the Africa Agenda 2063 strive for gender equality. Through a continental and national comparative analysis, we explored the aspiration and reality of women’s inequality under these two agendas. We assessed the degree and magnitude of the efforts (process) and performance (outcome) of AU member states in implementing SDG 5 of the UN Agenda 2030 and Aspiration 6 of Africa Agenda 2063. We employed a mixed-methods approach combining quantitative data analysis and qualitative case studies to provide a broad understanding of the factors influencing outcomes. We found that despite the efforts to achieve gender equality, the two agendas remained unfulfilled, indicating that the path to gender equality is still distant. With less than six years remaining until the completion of UN Agenda 2030, it is evident that gender equality will not be realised with the existing trend. To achieve gender equality in Africa in the next ten years, an annual increase of 4.9% is required, with political representation at 5.4%, civil society participation at 3.2%, and access to public services at a pace of 5.1%. Collective efforts from the African Union, its member states, and civil societies are crucial for realising gender equality in Africa.